2007
DOI: 10.1017/s0025315408000313
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between environmental variation and species abundance in shrimp community (Crustacea: Decapoda: Penaeoidea) in south-eastern Brazil

Abstract: The impact of shrimp fisheries in tropical regions has become comparable to the world's most intensively exploited temperate shelf ecosystems. The increase in the fishing fleet in south-eastern Brazil and the decrease in landings of profitable shrimp species have contributed to the incorporation of additional species into those fisheries. The goal of the present study is to investigate the influence of environmental factors on the abundance patterns of shrimp communities on the south-eastern coast of Brazil, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 16 publications
7
58
0
3
Order By: Relevance
“…A similar result was found by Rodrigues and Meira (1988), with the presence of the seabob shrimp in only 22 of the 77 analyzed stomachs of S. rastrifer and 2 of the 36 analyzed stomachs of S. basiliensis. It is known that penaeid shrimps are benthic and burry themselves in the sediment (Castilho et al, 2008;Simões et al, 2012), and therefore are available in a smaller scale for benthopelagic consumers, such as S. rastrifer and S. brasiliensis (Wakabara et al, 1993). Even if juveniles of X. kroyeri, are available in the pelagic zones for these fishes, they may be choosing to consume shrimp from the genus Acetes not only for their abundance in the studied environment, but for their short and blunt rostrum, that are of easier consumption than the sea-bob's rostrum with five teeth near the base and slightly curved upwards.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found by Rodrigues and Meira (1988), with the presence of the seabob shrimp in only 22 of the 77 analyzed stomachs of S. rastrifer and 2 of the 36 analyzed stomachs of S. basiliensis. It is known that penaeid shrimps are benthic and burry themselves in the sediment (Castilho et al, 2008;Simões et al, 2012), and therefore are available in a smaller scale for benthopelagic consumers, such as S. rastrifer and S. brasiliensis (Wakabara et al, 1993). Even if juveniles of X. kroyeri, are available in the pelagic zones for these fishes, they may be choosing to consume shrimp from the genus Acetes not only for their abundance in the studied environment, but for their short and blunt rostrum, that are of easier consumption than the sea-bob's rostrum with five teeth near the base and slightly curved upwards.…”
Section: Discussionmentioning
confidence: 99%
“…Since X. kroyeri has benthic habits, the availability of sediment types is important for their distribution (Costa et al 2007, Castilho et al 2008b once it provides protection against predators and minimizes energy cost when buried (Ameeri andCruz 1998, Simões et al 2010). Sediment of all sampling locations of the bay showed predominance of very fine sand.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on X. kroyeri populations of the northern coast of the state of São Paulo concluded that high temperature, salinity and very fine sand influenced the distribution of this species (Fransozo et al 2002, Costa et al 2007, Castilho et al 2008b. A relevant complementation for these findings would be a more detailed analysis of these populations involving demographic categories, since marine shrimps establish in areas with different environmental characteristics, according to their life stage (Dall et al 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Its life cycle is exclusively marine. Higher biomasses are found in salinities above 30 and at temperatures below 20°C (COSTA et al, 2004;MALLO, 2005;CASTILHO et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the biology of this species has also been obtained from the southeastern coast of Brazil, specifically from the state of São Paulo, including reports on the species' ecological distribution (COSTA et al, 2004), its reproductive biology (CASTILHO et al, 2008a) and the relationship between environmental variation and species abundance in the shrimp community (CASTILHO et al, 2008b). However, no studies on the variation between day and night in the catch and size of the South American red shrimp have yet been undertaken in any part of the area of its geographical distribution.…”
Section: Introductionmentioning
confidence: 99%